Surface-modified CMOS biosensors - Dehghandehnavi, Fahimeh; Sajal, Md. Sakibur; Dandin, Marc (Frontiers in Bioengineering and Biotechnology, 2024)
Biosensors translate biological events into electronic signals that quantify biological processes.They are increasingly used in in vitro diagnostics applications that leverage their ability to process small sample volumes. One recent trend has been to integrate biosensors with complementary metal-oxide semiconductor (CMOS) chips to provide enhanced miniaturization, parallel sensing, and low power consumption, at a low cost. CMOS-enabled biosensors are used in monitoring DNA hybridization, enzymatic reactions, and cell proliferation, to name a few applications. This paper explores the materials and processes used in emerging CMOS biosensors. We discuss subtractive and additive processes for creating electrodes for electrochemical sensing applications.We discuss functionalization techniques for creating bioelectronic interfaces that allow molecular events to be transduced into the electrical domain using a plurality of modalities that are readily provided by CMOS chips. Example modalities featured are optical sensing, electrochemical detection, electrical detection, magnetic sensing, and mechanical sensing.